AN ASSESSMENT OF STUDENT PERCEPTION ABOUT COACHING PERFORMANCE OF COLLEGE FEMALE DIRECTRESS SPORTS - Toshaba Channa; Syed Asim Hussain (The Sky)
The study about the skills, art and science of movement of human being is known as Physical education, it is necessary for whole educational procedure. The main purpose of PE is the progress of human being. It plays a significant part in the activity levels of athletes. Physical education not only fulfills a distinctive part in education, but is also an essential component of sports activities. In this paper a concise review of the research on students perception about the coaching performance of college female directress sports have been presented. Student ratings are most important to assess of teaching effectiveness, active contribution and meaningful participation from students can be significant in the success of such teaching assessment systems. For this purpose the total number of subjects N=90 girls students (45 each from BA part I and BA part II) were used as a sample of the study from nine G. G. D. C of Hyderabad city to assess the coaching performance of female directress sports. The five point Likert scale was applied to collect the data, which ranges from “strongly agrees” to “strongly disagree”. The outcome of the study concluded that generally the female Directress sports coaching techniques were better and they comprise the potential to exhibit, train, assess, and exact the techniques. The present study outcome may demonstrate that students are usually considered for progress in teaching to be the most important for the result of a teaching evaluation system. Furthermore, the result shows that through student’s feedback about coaching evaluations the course content and format can be developed. Students should be encouraged to participate in the coaching evaluation system because through this they will be able to provide significant opinion. Quality students participation is essential sign to improve teaching efficiency.